Natural Disasters Management and the Challenge of Governability in Indonesia. (September 2019) - Efendi, David; Agustiyara,; Putra, Husni Amriyanto
Since 1998, Indonesia has experienced a major transformation in the relationship between the rulers and the ruled. State–society relationships were previously subject-object, military-civilian, or superior-inferior. In other words, the state played a central role in all matters, while civil society 'Muhammadiyah' was limited to political and social activities. This tended to negatively impact community involvement in prevention and risk-reduction for natural disasters. This paper examines the role of civil society in disaster management in Indonesia. It does so in relation to the particular example of Yogyakarta, a special province where local values traditionally have more inherent authority than government-imposed law. The paper further discusses how there are important lessons for the future to be drawn from a Yogyakarta case study of how the national government has generally failed to build a private–public partnership and state–society relationship to deal with natural disasters based on local community needs.